Discontinuation of Folic Acid Supplementation in Young Patients With Sickle Cell Anemia. Issue 6 (August 2017) - Nguyen, Giang-Kim T.; Lewis, Angela; Goldener, Carol; Reed, Brenda; Dulman, Robin Yates; Yang, Elizabeth
Abstract : Folic acid (FA) is commonly prescribed for patients with sickle cell anemia, but evidence for the efficacy of this practice is lacking. We stopped FA supplementation and measured red blood cell folate levels after discontinuation of FA in 72 patients with clinically severe forms of sickle cell disease. We compared hemoglobin and reticulocyte counts before and after FA discontinuation in 51 of those patients, the majority of whom were on hydroxyurea. No patients had red blood cell folate levels below normal and no significant difference in hemoglobin levels ( P =0.18) or reticulocyte counts ( P =0.37) was found before and after FA discontinuation.